EMC pocket guide key EMC facts, equations and data - Wyatt, Kenneth; Jost, Randy (Edison, NJ SciTech Publishing, 2013)
The book is about electromagnetic compatibility and discusses EMC fundamentals, design, measurements and standards. Commonly used equations, miscellaneous information, and information about useful software is provided.
Electronic reproduction.
Keywords: Electromagnetic compatibility; Electronic books